PENGARUH KUALITAS PELAYANAN, DAYA SAING DESTINASI DAN PENGALAMAN SEBELUMNYA TERHADAP KEPUTUSAN BERKUNJUNG KEMBALI DENGAN KEPUASAN PENGUNJUNG SEBAGAI VARIABEL INTERVENING - Alvira Zulva Pallefi; Widiartanto Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2017)
Based on the need of vacation in the society nowdays, tourism industry offer many choices to fulfill it’s need. Beside, the tourism industry is a potential industry to support ecconomy. Goa Kreo as one of the natural tourism object in Semarang has many potentials but, there was a current condition where the number of visitor’s fluctuating. Goa Kreo is stimulating service quality, destination competitiveness, previous experience and tourist satisfaction to increase revisit intention in Goa Kreo.The aim of this study is to measure the influence of service quality, destination competitiveness, and previous experience toward revisit decision trough tourist satisfaction. The population of this resarch is visitors of Goa Kreo, while the sample is 100 visitor of Goa Kreo with some certain prerequirements. The data was analyzed using two-step analysis with SPSS 17.0 for windows where the validity test, reliability test,doefficient of correlation, coefficient of determination, test of significance (t-test and f-test) in advance has been done before.The result of this study is showing that service quality, destination competitiveness and previous experience has positive impact toward visitor satisfaction, where the biggest impact is own by previous experience. Based on the result of two-step analysis, tourist satisfaction is an intervening variable toward revisit decision in this study.Some recomendations are added based on those result. It’s recomended that hygine, security, and hospitality in Goa Kreo must be incerased. Moreover, it’s neccesary to increase destination competitiveness like facility’s maintenance and added up some general facility so that visitor will be satisfied with their experiences and willing to come back to Goa Kreo.